Contending with Our Racial Past in Medical Education: A Foucauldian Perspective. Issue 4 (8th August 2021) - Zaidi, Zareen; Partman, Ian M.; Whitehead, Cynthia R.; Kuper, Ayelet; Wyatt, Tasha R.
Abstract: Issue: Practices of systemic and structural racism that advantage some groups over others are embedded in American society. Institutions of higher learning are increasingly being pressured to develop strategies that effectively address these inequities. This article examines medical education's diversity reforms and inclusion practices, arguing that many reify preexisting social hierarchies that privilege white individuals over those who are minoritized because of their race/ethnicity. Evidence: Drawing on the work of French theorist Michel Foucault, we argue that medical education's curricular and institutional practices reinforce asymmetrical power differences and authority in ways that disadvantage minoritized individuals. Practices, such as medical education's reliance on biomedical approaches, cultural competency, and standardized testing reinforce a racist system in ways congruent with the Foucauldian concept of "normalization." Through medical education's creation of subjects and its ability to normalize dominant forms of knowledge, trainees are shaped and socialized into ways of thinking, being, and acting that continue to support racial violence against minoritized groups. The systems, structures, and practices of medical education need to change to combat the pervasive forces that continue to shape racist institutional patterns. Individual medical educators will also need to employ critical approaches to their work and develop strategies that counteract institutional systems of racial violence. Implications: A Foucauldian approach that exposes the structural racism inherent in medical education enables both thoughtful criticism of status-quo diversity practices and practical, theory-driven solutions to address racial inequities. Using Foucault's work to interrogate questions of power, knowledge, and subjectivity can expand the horizon of racial justice reforms in medicine by attending to the specific, pervasive ways racial violence is performed, both intra- and extra-institutionally. Such an intervention promises to take seriously the importance of anti-racist methodology in medicine.